Sun‐protection practices among undergraduates at an Australian University. (6th September 2015) - Shahnam, Adel; Samarawickrema, Indira; Ali, Sayed
Abstract: Background/Objectives: To assess the sun‐protection practices of undergraduates at the Australian National University. Methods: We sent emails with links to the questionnaire on the use of five sun‐protection practices in the last fortnight of the summer to 3341 randomly selected students aged 18–24 years in this cross‐sectional study. The response rate was 19% and 507 students met the inclusion criteria. Results: The sample consisted of 338 female and 169 male students with a mean age of 20.5 years (SD ± 1.9). Any method of sun protection was used always or often by 32% of respondents. The commonest method used was shade (58%) while the least common was wearing a hat (8%). Domestic students (44%) used sunglasses more than the international students (23%, P < 0.05) and female students used sunscreen (48%) and sunglasses (37%) more than male students (33% and 23% respectively) ( P < 0.05). In the 22–24‐year‐old age group non‐medical students (54%) used sunglasses more than the medical students (36%, P < 0.05). Conclusions: Only a third of the sample practiced any method of sun protection and there were significant differences in the practices between subgroups, suggesting they were at an increased risk of sun damage.